Implementation of Demonstration Method in Encouraging Students to Actively Learn in Fiqh Subjects at Madrasah Ibtidaiyah Maárif Gesing - Savira, Nia; Sakir, Moh; Stiya Mulyani, Pamungkas (DAS Institute, 2025)
This study aims to describe the implementation of the demonstration method in encouraging students to actively learn in the subject of fiqh at Madrasah Ibtidaiyah Ma'rif Gesing and the supporting and inhibiting factors of the implementation of the demonstration method in encouraging students to actively learn in the subject of fiqh at MI Ma'arif Gesing. The method used is descriptive qualitative, and data collection techniques include observation, interviews, and documentation. The results of the study indicate that the implementation of the demonstration method at MI Ma'arif Gesing has succeeded in encouraging student activity; students are not only active in following the material verbally but also actively participate in practice. This activity shows a sense of self-confidence and greater student involvement in learning. Despite challenges or obstacles, teachers are required to be more creative and patient in attracting students' attention. The implementation of this demonstration method has proven effective in encouraging students to actively learn. This study provides implications for the development of effective and efficient demonstration methods according to the age characteristics of MI first-grade class students